Antioxidant-guided isolation and mass spectrometric identification of the major polyphenols in barley (Hordeum vulgare) grain. (1st November 2016) - Gangopadhyay, Nirupama; Rai, Dilip K.; Brunton, Nigel P.; Gallagher, Eimear; Hossain, Mohammad B.
Highlights: Antioxidant-guided identification of significant polyphenols in barley was achieved. Antioxidant activities of flash chromatography fractions were based on four assays. Flavan-3-ols are strongest contributors to the antioxidant activity of barley. Quercetin and hydroxycinnamic acids are other contributors to its activity. A new flavan-3-ol derivative, catechin dihexoside, was detected. Abstract: In the present study, the relative contribution of individual/classes of polyphenols in barley, to its antioxidant properties, was evaluated. Flash chromatography was used to fractionate the total polyphenol extract of Irish barley cultivar 'Irina', and fractions with highest antioxidant properties were identified using total phenolic content and three in vitro antioxidant assays: DPPH, FRAP, and ORAC. Flavanols (catechin, procyanidin B, prodelphinidin B, procyanidin C) and a novel substituted flavanol (catechin dihexoside, C27 H33 O16 −, m/z 613.17), were identified as constituents of the fraction with highest antioxidant capacity. Upon identification of phenolics in the other active fractions, the order of most potent contributors to observed antioxidant capacity of barley extract were, flavanols > flavonols (quercetin) > hydroxycinnamic acids (ferulic, caffeic, coumaric acids). The most abundant polyphenol in the overall extract was ferulic acid (277.7 μg/g dw barley), followed by procyanidin B (73.7 μg/g dw barley).